2018
DOI: 10.17235/reed.2018.5431/2017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and progression of chronic kidney disease after a liver transplant: a prospective, real-life, observational, two-year multicenter study

Abstract: in the routine clinical practice, a moderate deterioration of renal function is frequent after liver transplantation. However, advanced chronic kidney disease is infrequent in patients with a good pre-transplant renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…It is unclear whether AKI after LT is the primary driver of poorer mortality outcomes or whether this is merely a correlation[ 166 ]. CKD is also a common complication after LT with an incidence ranging between 20% and 80%[ 167 , 168 ]. Numerous observations have implicated calcineurin-inhibitor (CNI) as a major risk factor of CKD in recipients of a transplant[ 169 - 171 ], and some studies have advocated the use of tacrolimus or mycophenolate mofetil instead of cyclosporin to reduce the incidence of chronic renal dysfunction after transplantation[ 170 , 172 ].…”
Section: Challenges Of Treating Hcc In Patients With Renal Dysfunctionmentioning
confidence: 99%
“…It is unclear whether AKI after LT is the primary driver of poorer mortality outcomes or whether this is merely a correlation[ 166 ]. CKD is also a common complication after LT with an incidence ranging between 20% and 80%[ 167 , 168 ]. Numerous observations have implicated calcineurin-inhibitor (CNI) as a major risk factor of CKD in recipients of a transplant[ 169 - 171 ], and some studies have advocated the use of tacrolimus or mycophenolate mofetil instead of cyclosporin to reduce the incidence of chronic renal dysfunction after transplantation[ 170 , 172 ].…”
Section: Challenges Of Treating Hcc In Patients With Renal Dysfunctionmentioning
confidence: 99%
“…Few studies are available for comparison with the Spanish series because of varying CKD definitions and follow-up periods, and of CKD stratification other than GFR below 60 mL/min/1.73 m 2 (stages III, IV, and V). In a recent study by Allen et al (10) the rate of stage-III CKD at 1 and 5 years was 50% and 49%, respectively, and that of stage-IV CKD was 4% and 5%, respectively; these figures are clearly higher, even at 1 year, than those described by Herrero et al, namely 30.8% at 1 year and 26.4% at 30 months for stage III, and 0.5% for stage IV within both periods (9). Furthermore, the percentage of patients with GFR ≥ 60 mL/min/1.73 m 2 (CKD stages I and II) was 42% and 32% at 1 and 5 years in the series by Allen et al, hence clearly lower than in the Spanish series, where rates of 68.8% and 73.1% at 1 year and 30 months, respectively, are reported.…”
mentioning
confidence: 68%
“…In this issue of The Spanish Journal of Gastroenterology (Revista Española de Enfermedades Digestivas), Herrero et al (9) discuss the evolution of renal function from the sixth month post-LT and over a period of 30 months in LT patients with preserved renal function at LT (GFR ≥ 60 mL/min/1.73 m 2 and no evidence of renal damage). Considering the concept of CKD as defined in the KDIGO guidelines, that is, as a GFR lower than 60 mL/min/1.73 m 2 , in the study by Herrero et al the rate of stage-III CKD at 2 years was 26.4%, and that of stage-IV CKD was 0.5%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Herrero et al (35) showed the key elements accounting for excellent renal function in the long term: good renal function before transplantation, stable CNI levels, minimization of CNI levels in patients with damaged renal function. One important variable in our study was the variation of the immunosuppression during co-administration of the 3D regimens, with higher trough levels at the beginning of antiviral therapy despite adjusting the CNI according to recommendations.…”
Section: Discussion Discussionmentioning
confidence: 99%